A preparatory study for carbon dioxide activation and revisitation of a crystallographic pitfall - Phull, Harminder (University of Ottawa (Canada), 2010)
Ruthenium beta-diketiminate complexes were studied in attempts to observe small molecule activation. [eta-p-cymene(iPrArNCMe) 2C]Ru[(iPrArNCMe)2CH] was prepared by the reaction of [RuCl2(p-cymene)]2 with 2 equivalents of [(iPrArNCMe)2CH]K in hexanes. The resulting complex was characterized by X-ray crystallography and 1 H NMR. Attempts to reduce the complex in-situ using potassium, sodium metal and sodium hydride afford [(iPrArNCMe) 2CH]Ru[eta5-1-methyl-4-(propan-2-ylidene)cyclohexa-2,5-dien-1-yl]. The resulting complex was characterized by X-ray crystallography and 1H NMR. The formation of [eta5-p-cymene( iPrArNCMe)2C]Ru[(iPrArNCMe)2CH] and [(iPrArNCMe)2CH]Ru[eta5-1-methyl-4-(propan-2-ylidene)cyclohexa-2,5-dien-1-yl] is attributed to nucleophilic attack and dehydrogenation of the pi-bound p-cymene ring respectively. While exploring small molecule activation on ruthenium systems a publication detailing the formation of an unprecedented Mg/Al-containing cluster [{R 2Al(mu-NSiMe3)(mu-OSiMe3)Mg(THF)2(mu- O2C)3]˙2 THF (R = Me (A), Et (B)) detailed the first end-on CO2 coordination to a d0 main group metal. This claim prompted a re-investigation of the complex and through detailed X-ray, DFT and NMR analysis the cluster is appropriated re-assigned as [{Me2Al(mu-OSiMe3) 2Mg(THF)2(mu-OCN)}]·1.5 THF.
Keywords: Chemistry, Physical.